Digital Economy in the Management System of Tourism Enterprises - FROLOVA, Victoria Borisovna; AVRAMENKO, Galina Mikhailovna; BESKOROVAYNAYA, Svetlana Anatolievna; SHELYGOV, Aleksandr Vladimirovich; MATYUNINA, Olga Evgenievna (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).17, 2019)
The article is devoted to the analysis of the digital economy in the management system of tourism enterprises. It has been established that the development of the digital economy in tourism provides an opportunity for communication and exchange of ideas and experience. It has been proved that Internet platforms allow combining efforts for the creation of tourism business, investment, as well as search for employees, partners, resources and markets of tourism services. It has been determined that digital technologies can also play a key role in the training of employees, knowledge sharing and implementation of innovative ideas, including in the tourism sector. The Russian education system is highlighted among the prerequisites for the development of the tourism industry, which has a high potential for training specialists in the digital economy since a person will focus mainly on the implementation of new opportunities in the digital economy.